Non-Muslim Consumer Perspective on Cosmetics and Personal Care Products - Mansor, Nusaibah; Shukri, Nurul Ajmal Mohd; Yahaya, Siti Norbaya (International Journal of Psychosocial Rehabilitation, 2020)
Majority of non-Muslim society believes that Halal is meant for Muslim only. Since they don’t have sufficient knowledge and awareness about halal products, the benefits of it is not well appreciated. After all, most of the company didn’t focus on non-Muslim market. The aim of this paper therefore is to determine the factors affecting purchase intention of Halal personal care products among non-Muslim consumer. Data was collected in Penang of 240 non-Muslims via structured questionnaire to gather information on their perspective towards Halal personal care products. Multiple Regression Analysis is applied to determine and assess the strength of relationship between variables. The factor that influences the purchase intention of Halal cosmetics and personal care products is halal awareness, religiosity, halal certification, attitude and brand trust. The result of the study suggest that brand trust strongly influences the purchase intention of Halal cosmetics and personal care products. Companies targeting non-Muslim markets are therefore are encouraged to tailor their marketing activities based on a behavioural perspective which increases and benefits social expectations and awareness which in turn would enhance their competitive advantage. By strengthening the brand trust through Halal process standard in production of guaranteeing hygiene and quality will allow products to penetrate into new market of non-Muslim consumer.